2017
DOI: 10.1016/j.ifacol.2017.08.1171
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-Decentralized Scheme for Integration of Price-Responsive Appliances in the Electricity Market

Abstract: A novel semi-decentralized control strategy is proposed for the integration in the power system of large populations of flexible loads, such as electric vehicles and "smart" appliances. To characterize the interactions between the single agents and their effects on the grid, a game theory framework is adopted. The price responsive appliances are modelled as competing players, characterizing a stable and efficient solution as a Nash equilibrium (no device has unilateral interest in changing its scheduled power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…These include EVs [26], [27], home storage devices [28], [29] and diesel generators [30], [31]. It should be noted that a comparable policy to that which we propose, applied to a continuum of devices, is also relevant in price-determined settings [32] and enables the coordination of devices within areas of flat prices.…”
Section: A Backgroundmentioning
confidence: 93%
“…These include EVs [26], [27], home storage devices [28], [29] and diesel generators [30], [31]. It should be noted that a comparable policy to that which we propose, applied to a continuum of devices, is also relevant in price-determined settings [32] and enables the coordination of devices within areas of flat prices.…”
Section: A Backgroundmentioning
confidence: 93%
“…It should be noted that the authors of [1] considered the task of directly assigning a piecewise constant input according to (8), but showed that this is suboptimal; (22) is in fact the correct way to convert (8) into discrete time. For the special case of a single store, the authors of [1] did propose a greedy policy that is equivalent to (22). Figure 1 describes a discrete time algorithm that implements the policy (22) as follows.…”
Section: Discrete Time Policy a Piecewise Constant Policymentioning
confidence: 99%
“…This allows us to study properties of the system in a general sense, without considering price dynamics in detail. However, a comparable policy to that which we propose, applied to a continuum of devices, is also relevant in such settings [22] and enables the coordination of devices within areas of flat prices. [14] is concerned with trading off the use of a battery and a diesel generator to support renewable resources, and uses constraints to ensure no mismatch between supply and demand.…”
Section: Problem Frameworkmentioning
confidence: 99%
“…We then iterate over this list to find the interval [y i−1 , y i ] that containsẑ fulfilling (20) and, if necessary, linearly interpolate between its limits. Having found z, we then allocate u according to (22). (b) Method for findingẑ using the energy balance of (20).…”
Section: Discrete Time Policy a Piecewise Constant Policymentioning
confidence: 99%
See 1 more Smart Citation